Is Herpes Simplex virus (HSV) a sign of Encephalitis in Iranian Newborns? Prevalence of HSV Infection in Pregnant Women in Iran: A Systematic Review and Meta-Analysis - ARABSALMANY, Masoumeh; BEHZADIFAR, Meysam; BARADARAN, Hamid Reza; TOGHA, Mansoureh; BEYRANVAND, Gholam; OLYAEEMANESH, Alireza; BEHZADIFAR, Masoud (Iranian Journal of Child Neurology, 2017)
How to Cite This Article: Arabsalmani M, Behzadifar M, Baradaran HR, Toghae M, Beyranvand Gh, Olyaeemanesh A, Behzadifar M. Is Herpes Simplex virus (HSV) a sign of Encephalitis in Iranian Newborns? Prevalence of HSV Infection in Pregnant Women in Iran: A Systematic Review and Meta-Analysis. Iran J Child Neurol.Spring 2017; 11(2):1-7. Abstract Objective Herpes Simplex virus (HSV) is one of the most common sexually transmitted diseases in the world. This study aimed to determine the prevalence of herpes simplex virus in pregnant women in Iran. Materials & Methods A systematic literature review was conducted to study the HSV subtypes in Persian and English papers through several databases. We searched Pub Med, Scopus, Ovid, Science Direct and national databases as Magiran, Iranmedex and Science Information Database (SID) up to October 2015. Random-effects model were applied to calculate the pooled prevalence of HSV subtypes. Results Five eligible studies were identified, including 1140 participants. The pooled prevalence of HSV infection in pregnant women was 0.64% (95% CI: 0.10- 1.18) in Iran. The pooled prevalence of studies on both HSV-1 and HSV-2 was 0.91% (CI: 0.81-1.02) and studies on only HSV-2 was 0.23% (CI: -0.61-0.63), respectively. Conclusion The prevalence of HSV infection in pregnant women in Iran was higher. HSV infection of the central nervous system, especially with HSV-2, can also cause recurrent aseptic meningitis and monophasic, as well as radiuculitis or myelitis. The performance of screening to detect infection in pregnant women can play an important role in the prevention and treatment of patients and help to prevent the transmission of HSV infection to infants in Iran. References 1.Xu F, Sternberg MR, Kottiri BJ, McQuillan GM, Lee FK, Nahmias AJ, et al. Trends in herpes simplex virus type 1 and type 2 seroprevalence in the United States. JAMA Neurol 2006; 296:964-73. 2.Bochner AF, Madhivanan P, Niranjankumar B, Ravi K, Arun A, Krupp K, et al. The Epidemiology of Herpes Simplex Virus Type-2 Infection among Pregnant Women in Rural Mysore Taluk, India. J Sex Transm Dis 2013; 2013:1-6. 3.Kulhanjian JA, Soroush V, Au DS, Bronzan RN, Yasukawa LL, Weylman LE, et al. Identification of women at unsuspected risk of primary infection with herpes simplex virus type 2 during pregnancy. N Engl J Med 1992; 326 :916–20. 4.Whitley RJ, Corey L, Arvin A, Lakeman FD, Sumaya CV, Wright PF, et al. Changing presentation of herpes simplex virus infection in neonates. J Infect Dis 1988; 158:109–16. 5.Cusini M, Ghislanzoni M. The importance of diagnosing genital herpes. J Antimicrob Chemother 2001; 47:9-16. 6.Cherpes TL, Meyn LA, Krohn MA, Lurie JG, Hillier SL. Association between acquisition of herpes simplex virus type 2 in women and bacterial vaginosis. Clin Infect Dis 2003; 37:319-25. 7.Gottlieb SL, Douglas JM, Schmid DS, Bolan G, Iatesta M, Malotte CK, et al. Seroprevalence and correlates of herpes simplex virus type 2 infection in five sexually transmitted–disease clinics. J Infect Dis 2002; 186:1381-9. 8.Arvaja M, Lehtinen M, Koskela P, Lappalainen M, Paavonen J, Vesikari T. Serological evaluation of herpes simplex virus type 1 and type 2 infections in pregnancy. J Sex Transm Infect 1999;75:168-71. 9.Brown ZA, Selke S, Zeh J, Kopelman J, Maslow A, Ashley RL, et al. The acquisition of herpes simplex virus during pregnancy. N Engl J Med 1997; 337:509-16. 10.Anzivino E, Fioriti D, Mischitelli M, Bellizzi A, Barucca V, Chiarini F, et al. Herpes simplex virus infection in pregnancy and in neonate: status of art of epidemiology, diagnosis, therapy and prevention. Virol J 2009; 6: 68-74. 11.Weiss H. Epidemiology of herpes simplex virus type 2 infection in the developing world. Herpes 2004;11:24-35. 12.Swetha G, Pinninti, David W, Kimberlin. Preventing HSV in the Newborn. Clin Perinatol 2014; 41:945–55. 13.Sheffield JS, Hill JB, Hollier LM, Laibl VR, Roberts SW, Sanchez PJ. Valacyclovir prophylaxis to prevent recurrent herpes at delivery: a randomized clinical trial. Obstet Gynecol 2006; 108:141-7. 14.Watts DH, Brown ZA, Money D, Selke S, Huang ML, Sacks SL. A double-blind, randomized, placebo-controlled trial of acyclovir in late pregnancy for the reduction of herpes simplex virus shedding and cesarean delivery. Am J Obstet Gynecol 2003; 188:836-43. 15.Bulletin AP. Clinical management guidelines for obstetrician-gynecologists. Obstet Gynecol 2003; 45:102- 13. 16.Curtis N, Finn A, Pollard A. Neonatal herpes simplex virus infections: where are we now? Hot Topics in Infection and Immunity in Children VII. 2nd ed. New York: Springer; 2011. P.146. 17.Allen UD, Robinson JL. Prevention and management of neonatal herpes simplex virus infections. Pediatr Child Health 2014;19:19-31. 18.Bernstein DI, Bellamy AR, Hook EW, Levin MJ, Wald A, Ewell MG, et al. Epidemiology, Clinical Presentation, and Antibody Response to Primary Infection With Herpes Simplex Virus Type 1 and Type 2 in Young Women. Clin Infect Dis 2013; 56:344-51. 19.Whitley R, Arvin A, Prober C, Corey L, Burchett S, Plotkin S, et al. Predictors of morbidity and mortality in neonates with herpes simplex virus infections. N Engl J Med 1991; 324:450-4. 20.Von Elm E, Altman DG, Egger M, Pocock SJ, Gotzsche PC, Vandenbroucke JP. The strengthening the reporting of observational studies in epidemiology (STROBE) statement: guidelines for reporting observational studies. Ann Intern Med 2007;147:573–7. 21.Higgins JP, Green S. Cochrane Handbook for Systematic Reviews of Interventions. 5thed. London, UK: The Cochrane Collaboration; 2011.P.420. 22.Danesh Shahraki A, Moghim S, Akbari P. Evaluation of the Serum Level of Herpes Simplex Type 2 Antibody among Pregnant Women in Shahid Beheshti Hospital, Isfahan. J Red Med Sci 2010;15:243. 23.Bagheri Josheghani S, Moniri R, Baghbani Taheri F, Sadat S, Heidarzadeh Z. The Prevalence of Serum antibodies in TORCH Infections during the First Trimester of Pregnancy in Kashan, Iran. Iran J Neonatol 2015; 6:8-12. 24.Ghasemi FS, Rasti S, Piroozmand A, Fakhrie-Kashan Z, Mousavi GA. Relationship between the prevalence of antibodies against cytomegalo, rubella, and herpes simplex viruses in women with spontaneous abortion compared to normal delivery. J Feyz 2015;19:86-92. 25.Pourmand D, Janbakhsh A, Hamzehi K, Dinarvand F, Ahmadi D. Seroepide Miological Study of Herpes Simplex Virus in Pregnant Women Referring to Health and Care Center in Kermanshah. J Kermanshah Univ Med Sci 2008;11:462-9. 26.Golalipour MJ, Khodabakhshi B, Ghaemi E. Possible role of TORCH agents in congenital malformations in Gorgan, northern Islamic Republic of Iran. East Mediterr Health J 2009;15:330-6. 27.Chen KT, Segu M, Lumey LH, Kuhn L, Carter RJ, Bulterys M, et al. Genital herpes simplex virus infection and perinatal transmission of human immunodeficiency virus. Obstet Gynecol 2005; 106:1341-8. 28.Ali S, Khan FA, Mian AA, Afzal MS. Seroprevalence of cytomegalovirus, herpes simplex virus and rubella virus among pregnant women in KPK province of Pakistan. J Infect Dev Ctries 2014;18:389-90. 29.Hezarjaribi HZ, Fakhar M, Shokri A, Teshnizi SH, Sadough A, Taghavi M. Trichomonas vaginalis infection among Iranian general population of women: a systematic review and meta-analysis. Parasitol Res 2015;114:1291- 300. 30.Sauerbrei A, Wutzler P. Herpes simplex and varicella-zoster virus infections during pregnancy: current concepts of prevention, diagnosis and therapy. Part 1: herpes simplex virus infections. Med Microbiol Immunol 2007; 196:89–94 31.Büchner S, Erni P, Garweg J, Gerber S, Kempf W, Lauper U, et al. Swiss recommendations for the management of genital herpes and herpes simplex virus infection of the neonate. Swiss Medi Wkly 2004; 134:205–214 32.Meerbach A, Sauerbrei A, Meerbach W, Bittrich HJ, Wutzler P. Fatal outcome of herpes simplex virus type 1-induced necrotic hepatitis in a neonate. Med Microbiol Immunol 2006; 195:101–105 33.Tyler KL. Herpes simplex virus infections of the central nervous system: encephalitis and meningitis, including Mollaret’s. Herpes 2004. ; 11:57A-64A 34.Corey L, Whitley RJ, Stone EF, Mohan K. Difference between herpes simplex virus type 1 and type 2 neonatal encephalitis in neurological outcome. Lancet 1988; 1:1-4 35.Berger JR, Houff S. Neurological complications of herpes simplex virus type 2 infection. Arch Neurol 2008.; 65:596-600 36.Gallo MF, Warner L, Macaluso M, Stone KM, Brill I, Fleenor ME. Risk factors for incident herpes simplex type 2 virus infection among women attending a sexually transmitted disease clinic. J Sex Transm Dis 2008; 35:679–85. 37.Riley LE. Herpes simplex virus. Semin Perinatal 1998; 22:284-92. 38.Lankarani KB, Alavian SM, Peymani P. Health in the Islamic Republic of Iran, challenges and progresses. Med J Islamic Repub Iran 2013; 27:42. 39.Hoaglin DC. Assessment of heterogeneity in meta-analyses. JAMA Neurol 2014; 312:2286-7.